Charge trapping at the dielectric of organic transistors visualized in real time and space - Mathijssen, Simon G. J.; Kemerink, Martijn; Sharma, Abhinav; Cölle, Michael; Bobbert, Peter A.; Janssen, René A. J.; Leeuw, Dago M. de (Advanced materials, 2008)
Scanning Kelvin probe microscopy demonstrates that water-induced charge trapping at the SiO2 dielectric - visualized in real time and space - is responsible for the commonly observed gate-bias-induced threshold-voltage shift in organic field-effect transistors. When a bias is applied to the electrodes, charges are injected onto the SiO2 (see background of the figure). When the contacts are grounded, the charges are released again (foreground picture).